SAT0255 Predictive and protective role of adipokines in radiographic spinal progression in patients with ankylosing spondylitis. (23rd January 2014) - Poddubnyy, D.; Neumann, E.; Junker, S.; Frommer, K.; Haibel, H.; Conrad, K.; Rudwaleit, M.; Müller-Ladner, U.; Sieper, J.; Syrbe, U.
Abstract : Background: Adipokines are adipose-derived peptides with potent modulatory actions on immune cells and target tissues involved in ankylosing spondylitis (AS), including cartilage and bone. Nonetheless, there are nearly no data on relationship between adipokines and inflammation and new bone formation in AS. Objectives: To investigate the association of adipokines with radiographic progression in the spine (new syndesmophytes formation or growth of the existing syndesmophytes) in patients with AS. Methods: Altogether 86 patients with AS from the German Spondyloarthritis Inception Cohort (GESPIC) were included in the analysis. Radiographs of the lumbar and cervical spine performed at baseline and after 2 years of follow-up were centrally collected, digitized, and subsequently scored independently by two trained readers. Serum levels of C-reactive protein (CRP) were measured at baseline and every 6 months thereafter, a time-averaged value was calculated. Serum levels of adiponectin, resistin and visfatin were measure in baseline serum samples. Threshold for elevated/non-elevated levels of adipokines were chosen on the basis of median values. Results: Radiographic spinal progression was noted in 28 patients (33%). Serum level of adiponectin was significantly lower and level of visfatin significantly higher in progressors as compared to patients without radiographic spinal progression over two years (table). Elevated level of adiponectin (>12100 ng/ml) was protective regarding radiographic spinal progression: odds ratio (OR) for progression =0.22, 95%CI 0.08-0.61, p=0.003 that was also confirmed in the multivariate logistic regression analysis after adjustment for the baseline radiographic damage and CRP level: OR=0.18, 95%CI 0.06-0.59, p=0.004. Elevated level of visfatin (>5.6 ng/ml) was, in contrast, predictive regarding radiographic spinal progression (OR=2.6, 95%CI 1.0-6.5, p=0.049), although the statistical significance was lost in the multivariate analysis. A predictive trend only was observed for resistin. There was no significant correlation of adiponectin and visfatin levels with acute phase reactants (CRP, erythrocyte sedimentation rate); resistin showed weak correlation with CRP (rho =0.23, p=0.03) and moderate correlation with visfatin (rho =0.54, p<0.001), Importantly, in a subgroup of patients with persistent systemic inflammation (time averaged CRP >6 mg/l) adiponectin retained its protective value regarding radiographic progression: OR=0.19, 95%CI 0.05-0.69, p=0.012. Conclusions: Adiponectin plays a protective and visfatin a predictive role regarding radiographic spinal progression in AS, which seems to be independent from activity of systemic inflammation. Disclosure of Interest: None Declared